Impact of microfinance on the efficiency of maize producers in North Eastern Nigeria - Auwal, Ahmed Muhammad (2017)
Access to credit is vital in agricultural production due to low income from both farming and non-farm undertakings and this impedes investing in production inputs especially among smallholder farmers. These farmers produced about 90% of the total food supply, but the production has been declining over the last few years due to lack of funding, a situation that subjects them to low efficiency, low output and income which aggravates poverty in the country. Microfinance as an alternative means of providing financial services to the poor, have the potential to increase their income which if well spend on farm inputs could eventually increase their well-being.